Hubungan Efikasi Diri Dengan Stress Keluarga Dimasa New Normal Covid-19 - Yusrini Yusrini; Wiwie Herdalisa; Resti Yuli Oktavia (Universitas Malahayati, 2023)
ABSTRACT The new normal period is an effort to return the lives of citizens to normal with new adaptations as an effort to save people's lives and keep the country empowered to carry out its functions. So as not to cause emotional and physical and psychological pressure. Efforts to overcome family stress in the new normal, one of which is by getting back up after going through the covid-19 pandemic. Families need to have good self-efficacy. Self-efficacy is an individual's belief in his ability to be able to control and carry out tasks in order to achieve a goal. To purpose provide an overview of the relationship between self-efficacy and family stress in the new normal period of covid-19. This type of research is quantitative with a descriptive quantitative research design with a cross sectional approach, namely the variables in the research object are measured or collected at the same time. The sample size is 256 people. The sampling technique used in this research is random sampling. The results of the statistical test of the relationship between self-efficacy and family stress in the new normal covid- 19 through the chi square test obtained p-value = 0.000, p value < (0.05) which means H0 is rejected, so it can be concluded that there is a significant relationship between self-efficacy and family stress in the new normal covid-19. Based on the results of this study, there is a significant relationship between self-efficacy and family stress during the new normal covid-19. It is hoped that further researchers will develop research to look for educational factors that cause the relationship between self-efficacy and family stress in the new normal covid-19. Keywords: Self-Efficacy, Covid-19, New Normal, Family Stress ABSTRAK Masa new normal merupakan upaya mengembalikan kehidupan warga secara normal dengan adaptasi baru sebagai upaya menyelamatkan hidup warga dan menjaga negara agar tetap bisa berdaya menjalankan fungsinya. Agar tidak menimbulkan emosi dan tekanan fisik maupun psikologisnya. Upaya untuk mengatasi stress keluarga dimasa new normal, salah satunya dengan bangkit kembali setelah melewati pandemi covid-19. Keluarga perlu memiliki efikasi diri yang baik. Efikasi diri adalah keyakinan individu akan kemampuan yang dimilikinya untuk dapat mengendalikan serta menjalankan tugas guna tercapainya suatu tujuan. Tujuan penelitian untuk memberikan gambaran tentang Hubungan Efikasi Diri Dengan Stress Keluarga Dimasa New normal covid-19. Jenis penelitian ini adalah kuantitatif dengan desain penelitian ini adalah deskriptif kuantitatif dengan pendekatan secara cross sectional yaitu variable pada objek penelitian diukur atau dikumpulkan kala waktu yang bersamaan. Besar sampel yaitu 256 orang. Tehnik sampling yang digunakan pada penelitian ini adalah random sampling. Hasil uji statistik hubungan efikasi diri dengan stress keluarga dimasa new normal covid-19 melalui uji chi square didapatkan p-value = 0,000, nilai p < α (0,05) yang artinya H0 ditolak, sehingga didapatkan kesimpulan bahwa ada hubungan yang signifikan antara efikasi diri dan stress keluarga dimasa new normal covid-19. Berdasarkan hasil penelitian ini bahwa adanya hubungan yang signifikan antara efikasi diri dan stress keluarga dimasa new normal covid-19. Diharapkan bagi peneliti selanjutnya mengembangkan penelitian untuk mencari faktor pendidikan yang menyebabkan hubungan efikasi diri dengan stress keluarga dimasa new normal. Kata Kunci: Efikasi Diri, Covid-19, New Normal, Stress Keluarga